School Personnel and Parents' Concerns Related to COVID-19 Pandemic's Impact Related to Schools. Issue 4 (2nd October 2021) - Anderson, Jacqueline R.; Hughes, Jennifer L.; Trivedi, Madhukar H.
Abstract: In March 2020, the majority of schools in the United States transitioned to distance learning in order to reduce the spread of COVID-19. Little data is available on the impact of this abrupt transition on youth, but many experts have expressed concerns about the implications of this major change in schooling on mental health and academic outcomes. The current study sought to gain insight on parent and school personnel (n = 515, n = 193) concerns about the impact of the COVID-19 pandemic related schools and the return to school within two cohorts (summer 2020, fall 2020). Primary concerns were student health, student academic development, personal health, and student mental health. These findings may assist schools in their preparation for the transitions related to COVID-19 and changes in the school year to provide resources for their families to promote their students' development and support their school personnel's health. Impact Statement The current study can assist school policy makers in considering how to address concerns and fears related to the COVID-19 pandemic for parents and school personnel. The findings can assist school mental health professionals in preparing to address potential school personnel and parent concerns related to the COVID-19 pandemic. School psychologists are going to be challenged to adapt their services based on concerns related to the pandemic; these findings may assist them in adapting those services to address the common concerns and fears of school personnel and parents.